MFRS 141: Determinants and extent of disclosure - Aliana Shazma Amir, Amir (2014)
The objective of this study is two-fold. First, the study investigates the extent of the agriculture accounting disclosure as prescribed by Malaysian Financial Reporting Standard, MFRS 141 among Malaysian listed companies for years 2009 and 2012. Second, this study intends to examine the factors that influence the company's disclosure on MFRS 141 by using 82 firm-year observations. This study found that the level of compliance on MFRS 141 among all plantation companies has marginally improved from 80 percent in 2009 to 83 percent in 2012. Based on content analysis of the standard, it is discovered that paragraphs 47 to 54 are the most difficult paragraphs to comply with as these paragraphs require the preparer to be well versed with fair value measurement. The results on logit regression analysis indicate that profitability as measured by earnings per share significantly influence the level of compliance score on MFRS 141. Likewise, company size as measured by market value of equity has significantly affect compliance score at 5 percent level. There is no evidence that other variables such as a) age; (b) leverage; (c) directors' ownership, (d) foreign ownership; (e) growth and (f) auditors quality have any significant influence on the level of compliance on MFRS 141. It is hopeful that this finding could help regulators and standard setting bodies in providing adequate guidelines to financial statement preparers in the future